The Role Of Information Technology In Promoting Accounting Disclosure -Study Applied For A Sample Of Professionals For The Year 2019- (Journal of Economic Additions, 2019)
This study aims to address the role of information technology in promoting accounting disclosure in the financial statements, this study has been addressed in two parts, a theoretical was the briefing aspects of theoretical disclosure of accounting and information technology another application of the questionnaire for professionals about the contribution of information technology in promoting accounting disclosure in financial statements, and the study was based on two program (MS EXCEL) and (SPSS), and after the statistical treatment of the questionnaire directed to a sample of professionals in the south-eastern Algeria, we have reached the important role of information technology in enhancing the disclosure Accounting in the financial statements by increasing economic entities, owners and users of financial statements.Key words: information technology; promoting accounting; financial statementsJel Classification codes: M41.